VATTIMO, G. Dopo la cristianita: per un cristanesimo non religioso. Milano: Garzanti, 2002. - Costa, Claudio F. (Princípios: Revista de Filosofia (UFRN), 2010)
Resenha do livro de: COLLIN, McGinn, The Making ofa Philosopher: My Journey through Twentieth-Centurv Philosophy. New York: Harper Collins, 2002. 241 paginas.